2016
DOI: 10.1016/j.cortex.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Targeting alertness to improve cognition in older adults: A preliminary report of benefits in executive function and skill acquisition

Abstract: Efficient self-regulation of alertness declines with age exacerbating normal declines in performance across multiple cognitive domains, including learning and skill acquisition. Previous cognitive intervention studies have shown that it is possible to enhance alertness in patients with acquired brain injury and marked attention impairments, and that this benefit generalizes to improvements in more global cognitive functions. In the current preliminary studies, we sought to test whether this approach, that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 142 publications
(220 reference statements)
0
17
0
Order By: Relevance
“…The early detection of cognitive deficits may have implications in pharmaceutical and rehabilitation interventions. To date, pharmaceutical and rehabilitation interventions are initiated after significant changes in cognitive functions are observed (Connolly & Lang, 2014;Van Vleet et al, 2016). Previous studies showed that cognitive function could be improved through cognitive rehabilitation interventions (Van Vleet et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The early detection of cognitive deficits may have implications in pharmaceutical and rehabilitation interventions. To date, pharmaceutical and rehabilitation interventions are initiated after significant changes in cognitive functions are observed (Connolly & Lang, 2014;Van Vleet et al, 2016). Previous studies showed that cognitive function could be improved through cognitive rehabilitation interventions (Van Vleet et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To date, pharmaceutical and rehabilitation interventions are initiated after significant changes in cognitive functions are observed (Connolly & Lang, 2014;Van Vleet et al, 2016). Previous studies showed that cognitive function could be improved through cognitive rehabilitation interventions (Van Vleet et al, 2016). Although the benefits of these interventions have been proven in older adults (Van Vleet et al, 2016), their effectiveness may vary among individuals depending on their mental state at the moment of the training.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sustained attention seems to be impaired in most patients with MCI . In addition, sustained attention is affected by alertness, which is critical for effective executive function . Both attention and executive function are multidimensional and highly complex cognitive constructs, and they are considered as being intimately related .…”
Section: Discussionmentioning
confidence: 99%
“…However, the feasibility of attention training in clinical practice/implication may be an issue. Because the attentional deficits appear quite early on in cognitive disease and underlie many difficulties in activities of daily living, the maintenance of attention is effortful, variable, and prone to decline . However, the multidomain attention training, as compared with single attention training, may adapt to different stimuli in daily life and decrease relevant risks, such as during driving and falling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation